ASUHAN KEPERAWATAN PADA KLIEN HIPERTENSI DENGAN MASALAH NYERI AKUT - Linda Wulandari (2023)
Background : Hypertension is a condition of increasing systolic blood pressure in the body of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. Objective : This research was conducted to gain experience and know a real description of the provision of nursing care to hypertensive clients which includes assessment, nursing diagnoses, nursing plans, nursing implementation and nursing evaluation. Method : The research design used is the case study method. Data collection was carried out using interviews, observation, physical examination and documentation studies. Results : The nursing problems found in hypertensive clients are acute pain related to physiological injury agents, sleep pattern disturbances related to environmental barriers and ineffective health care related to making appropriate judgments. After carrying out nursing actions for 4 x 24 hours with the results of the evaluation of all nursing problems resolved. Conclusion :The application of nursing care to clients with hypertension achieves the expected results.